In silico Prediction, Characterization, Molecular Docking, and Dynamic Studies on Fungal SDRs as Novel Targets for Searching Potential Fungicides Against Fusarium Wilt in Tomato - Aamir, Mohd; Singh, Vinay Kumar; Dubey, Manish Kumar; Meena, Mukesh; Kashyap, Sarvesh Pratap; Katari, Sudheer Kumar; Upadhyay, Ram Sanmukh; Umamaheswari, Amineni; Singh, Surendra (Frontiers in Pharmacology, 2018)
Vascular wilt, caused by Fusarium oxysporum f.sp. lycopersici (FOL) is one of the most devastating diseases, delimiting the tomato production worldwide. Fungal short chain dehydrogenases/reductases (SDRs) are NADP(H) dependent oxidoreductases, having shared motifs and common functional mechanism, have been demonstrated as biochemical targets for commercial fungicides. The 1,3,6,8 tetra hydroxynaphthalene reductase (T4HNR) protein, a member of SDRs family, catalyzes the naphthol reduction reaction in fungal melanin biosynthesis. We retrieved an orthologous member of T4HNR, (complexed with NADP(H) and pyroquilon from Magnaporthe grisea) in the FOL (namely; FOXG_04696) based on homology search, percent identity and sequence similarity (93% query cover; 49% identity). The hypothetical protein FOXG_04696 (T4HNR like) had conserved T-G-X-X-X-G-X-G motif (cofactor binding site) at N-terminus, similar to M. grisea (1JA9) and Y-X-X-X-K motif, as a part of the active site, bearing homologies with two fungal keto reductases T4HNR (M. grisea) and 17-β-hydroxysteroid dehydrogenase from Curvularia lunata (teleomorph: Cochliobolus lunatus PDB ID: 3IS3). The catalytic tetrad of T4HNR was replaced with ASN115, SER141, TYR154, and LYS158 in the FOXG_04696. The structural alignment and superposition of FOXG_04696 over the template proteins (3IS3 and 1JA9) revealed minimum RMSD deviations of the C alpha atomic coordinates, and therefore, showed their structural conservation. The best protein model was docked with 37 fungicides, to evaluate their binding affinities, with FOXG_04696. The Glide XP and YASARA docked complexes showed discrepancies in results for scoring and ranking the binding affinities of the selected fungicides. The docked complexes were further refined and rescored through 50 ns long MD simulations, and binding free energies (∆Gbind) calculations, starting from the docked poses, using MM/GBSA analysis, which revealed Oxathiapiprolin and Famoxadone as better fungicides. However, Famoxadone had better interaction of the docked residues, with best protein ligand contacts, minimum RMSD (high accuracy of the docking pose) and RMSF (structural integrity and conformational flexibility of docking), at the specified docking site. The Famoxadone was found to be acceptable based on in silico toxicity and in-vitro growth inhibition assessment. We conclude that the FOXG_04696 could be employed as a novel candidate for structure-based design and screening of target fungicides against the FOL pathogen.